Pengaruh Terapi Kognitif: Relaksasi Napas Dalam Terhadap Tingkat Stress Dalam Menjalani Skripsi Pada Mahasiswa Ekstensi Kelas 2B Di UIMA Tahun 2022: Effects of Cognitive Therapy: Deep Breathing Relaxation Against Stress Levels Undergoing a Thesis for Class 2B Extension Students at UIMA in 2022 - Rais, Ratno Arif (Dohara POAJ, 2023)
Introduction: One of the requirements for finishing a bachelor’s degree is writing a thesis which often makes the students stressed. The level of stress varies from normal to moderate. One of the techniques to handle stress is cognitive therapy; deep breathing relaxation. This study aims to find out the difference in the stress level before and after cognitive therapy; deep breathing relaxation for the students. Methods: This study used the quasi-experimental method which is a one-group pretest-posttest design without a control group experimental study method. The sample of the study was taken with simple random sampling from extension students 2B in UIMA 2022 for 15 respondents. The measuring instrument was using Depression Anxiety Stress Scale 42 (DASS 42) which has been adjusted. The data analysis used paired sample t-test to show the average stress level before and after the cognitive therapy; deep breathing relaxation. Result: The study showed a decreasing level with a 0,000 < 0,05 p-value, meaning there is a significant difference before and after the therapy. The result shows that after the cognitive therapy; deep breathing relaxation, there is a decreasing stress level from a moderate level for 7 (46,7%) respondents, to a majority of normal for 8 (53,3%) respondents. Discussion: There is a significant effect of cognitive therapy; deep breathing relaxation towards the stress level of extension students.